IMPLEMENTATION OF GROUP GUIDANCE BASED ON MULTIPLE INTELLIGENCES TO DEVELOP EMOTIONAL AWARENESS AND INTERPERSONAL COMMUNICATION IN EARLY CHILDHOOD - Putri Fakhrina Sari; Helnita; Raudha Meutia; Tria Marvida; Liza Fidiawati (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to describe the implementation of Multiple Intelligences-based group guidance services in developing emotional awareness and interpersonal communication in early childhood. This study uses a qualitative approach with a case study design. A total of 12 children aged 5-6 years and 2 PAUD teachers in Banda Aceh were the subjects in this study. Data collection was carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model. The results of the study indicate that the integration of interpersonal intelligence in group guidance activities helps children recognize and express emotions verbally and there is an increase in interpersonal communication skills in the form of active listening, empathy, and cooperation with peers. This study provides conceptual and practical contributions to the development of group guidance services based on developmental psychology theory in the context of early childhood education.